2011
DOI: 10.1186/1471-2334-11-181
|View full text |Cite
|
Sign up to set email alerts
|

Does prolonged β-lactam infusions improve clinical outcomes compared to intermittent infusions? A meta-analysis and systematic review of randomized, controlled trials

Abstract: BackgroundThe emergence of multi-drug resistant Gram-negatives (MDRGNs) coupled with an alarming scarcity of new antibiotics has forced the optimization of the therapeutic potential of available antibiotics. To exploit the time above the minimum inhibitory concentration mechanism of β-lactams, prolonging their infusion may improve outcomes. The primary objective of this meta-analysis was to determine if prolonged β-lactam infusion resulted in decreased mortality and improved clinical cure compared to intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 33 publications
1
78
0
3
Order By: Relevance
“…Rather than simply adding a second agent, optimization of antimicrobial therapy includes selection of appropriate antibiotic agent(s), dose, frequency, route, and duration. It also may include prolonged antibiotic infusion strategies to exploit the time above the MIC mechanism of ␤-lactams when combating organisms with elevated MICs (239,242).…”
Section: Resultsmentioning
confidence: 99%
“…Rather than simply adding a second agent, optimization of antimicrobial therapy includes selection of appropriate antibiotic agent(s), dose, frequency, route, and duration. It also may include prolonged antibiotic infusion strategies to exploit the time above the MIC mechanism of ␤-lactams when combating organisms with elevated MICs (239,242).…”
Section: Resultsmentioning
confidence: 99%
“…Recent metaanalyses that focused on beta-lactams (Table 3) have mostly concluded that existing data were favorable for the use of specific or all beta-lactam agents by prolonged or continuous infusion in terms of clinical outcomes. Although 2 of these studies did not observe a clinical advantage for using continuous or extended schedules (93,97), the investigators acknowledged the many limitations of the studies included and the need for the larger, multicenter randomized control trials.…”
Section: Contemporary Studiesmentioning
confidence: 99%
“…Although quite a few of these have been conducted over time, they differ markedly in their inclusion/exclusion criteria, thus not necessarily allowing elucidation of the true effectiveness of nontraditional beta-lactam dosing regimens (4,18,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102). Recent metaanalyses that focused on beta-lactams (Table 3) have mostly concluded that existing data were favorable for the use of specific or all beta-lactam agents by prolonged or continuous infusion in terms of clinical outcomes.…”
Section: Contemporary Studiesmentioning
confidence: 99%
“…Nevertheless, different meta-analyses evaluating CI versus STI of various time-dependent antimicrobials have failed to convincingly demonstrate improved clinical outcomes on mortality and clinical cure (1)(2)(3)(4)(5)(6). It is noteworthy, however, that in the majority of studies included in these metaanalyses, the total daily dose of antimicrobials was lower for patients treated with EI or CI (1,2,5).…”
mentioning
confidence: 89%